Late complications after brachytherapy of I-125 uveal melanoma - Kowal, Joanna; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Purpose : To assess the late complications after the I-125 brachytherapy of uveal melanoma. Material and methods : 129 patients (71 women – 55%, and 58 men – 45%) treated at the Department of Ophthalmology and Ocular Oncology of the University Hospital in Krakow between January 2005 and December 2009 were evaluated. I-125 isotope applicators were used for tumor irradiation. The mean follow-up was 42.5 months. Results : The following complications were observed: radiation cataract, secondary glaucoma, radiation retinopathy, radiation maculopathy, necrosis of sclera, retinal and vitreous hemorrhages and retinal detachment. Post-radiation cataract was the most common late complication (90.5–94.7%). Conclusions : Despite the undoubted effectiveness in the treatment of uveal melanomas, I-125 brachytherapy poses a high risk of complications. Tumor location in the proximity of critical visual structures negatively affected ultimate visual function. The tumor size and the dose of irradiation significantly affected the incidence of radiation-induced complications.